Early Allograft Dysfunction Increases Hospital Associated Costs After Liver Transplantation—A Propensity Score–Matched Analysis. Issue 3 (5th December 2020) - Moosburner, Simon; Sauer, Igor M.; Förster, Frank; Winklmann, Thomas; Gassner, Joseph Maria George Vernon; Ritschl, Paul V.; Öllinger, Robert; Pratschke, Johann; Raschzok, Nathanael
Abstract : Concepts to ameliorate the continued mismatch between demand for liver allografts and supply include the acceptance of allografts that meet extended donor criteria (ECD). ECD grafts are generally associated with an increased rate of complications such as early allograft dysfunction (EAD). The costs of liver transplantation for the health care system with respect to specific risk factors remain unclear and are subject to change. We analyzed 317 liver transplant recipients from 2013 to 2018 for outcome after liver transplantation and hospital costs in a German transplant center. In our study period, 1‐year survival after transplantation was 80.1% (95% confidence interval: 75.8%‐84.6%) and median hospital stay was 33 days (interquartile rage: 24), with mean hospital costs of €115, 924 (SD €113, 347). There was a positive correlation between costs and laboratory Model for End‐Stage Liver Disease score (rs  = 0.48, P  < 0.001), and the development of EAD increased hospital costs by €26, 229. ECD grafts were not associated with a higher risk of EAD in our cohort. When adjusting for recipient‐associated risk factors such as laboratory Model for End‐Stage Liver Disease score, recipient age, and split liver transplantation with propensity score matching, only EAD and cold ischemia increased total costs. Conclusion: Our data show that EAD leads to significantly higher hospital costs for liver transplantation, which are primarily attributed to recipient health status. Strategies to reduce the incidence of EAD are needed to control costs in liver transplantation.